Working during school and academic performance - Todd R. Stinebrickner; Ralph Stinebrickner (The University of Western Ontario, Department of Economics, 2000)
Unique new data from a college with a mandatory work-study program are used to examine the relationship between working during school and academic performance. Particular attention is paid to the importance of biases that are potentially present because the number of hours that are worked is endogenously chosen by the individual. The results suggest that, even if results appear reasonable, a researcher should be cautious when drawing policy conclusions about the relationship between hours worked and a particular outcome of interest unless he or she is confident that potential problems associated with the endogeneity of hours have been adequately addressed.
Keywords: 330; Studium; Nebentätigkeit; Studienfinanzierung; Statistischer Test; Kalifornien; USA